PERAN PERCEIVED ORGANIZATIONAL SUPPORT SEBAGAI VARIABEL INTERVENING DALAM PENGARUH QUALITY OF WORK LIFE TERHADAP PERILAKU ORGANIZATIONAL CITIZENSHIP BEHAVIOR PEGAWAI DPMPTSP PROVINSI GORONTALO : THE ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT AS AN INTERVENING VARIABLE IN THE INFLUENCE OF QUALITY OF WORK LIFE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF EMPLOYEES OF DPMPTSP OF GORONTALO PROVINCE - Dontili, Fikawati; Podungge, Robiyati; Tantawi, Rezkiawan (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
This study aimed to analyze the direct influence of Quality of Work Life (QWL) on Organizational Citizenship Behavior (OCB), Quality of Work Life on Perceived Organizational Support (POS), and Perceived Organizational Support on Organizational Citizenship Behavior. Also, it aimed to analyzed the role of Perceived Organizational Support in mediating Quality of Work Life on Organizational Citizenship Behavior among DPMPTSP (One-Stop Investment and Integrated Services Office) employees of Gorontalo Province. This study employed a descriptive quantitative approach, where is data were collected through a questionnaire distributed to 45 Civil Servants (ASN) employees within the DPMPTSP of Gorontalo Province, using a census technique. Data analysis was conducted using inferential statistical methods, namely Partial Least Square-Structural Equation Modeling (PLS-SEM) version 4.0. The findings indicated that QWL did not signify a direct infulence on OCB but had a significant influence on POS. Futhermore, POS influence OCB significantly and was able to fully mediate the relationship between QWL and OCB. These findings highlighted the importance of designing human resource policies that focus not only on structural and administrative aspects but also creating a supportive and emotionally oriented work climate.